Conjugated polymers containing naphthalimide units with ethylene glycol side chains, methods of making and applications in zinc ion battery
Patent Information
- Application Number
- CN202611044499.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-13
AI Technical Summary
[0004]本发明针对现有水系锌离子电池负极保护层中保护层材料离子传导效率低、亲疏水性失衡、保护效果欠佳等问题,导致锌负极难以实现长期循环稳定性
[0021]1、本发明的含有乙二醇侧链的萘酰亚胺单元的共轭聚合物,以萘酰亚胺单元和噻吩或噻唑为分子主链,即完全由π单元通过单键连接而成,侧链为极性乙二醇短链,共轭聚合物的主链赋予其疏水特性,可有效隔离锌负极与水分子的直接接触,从而抑制析氢腐蚀等副反应;其低聚乙二醇侧链则赋予材料亲锌性,不仅促进了Zn2+的传导,同时也平衡了主链的疏水效应,使得界面层整体兼具亲锌与疏水的双重功能。亲锌的乙二醇链段加速了Zn2+的迁移,而疏水主链则将[Zn(H2O)6]2+中的水分子阻挡于隔膜之外,从而显著促进了Zn2+的去溶剂化过程。聚合物的共轭骨架所形成的共轭电子结构,赋予了其适当的电子电导率,从而有效调控了电极/电解液界面的电场分布;这一特性不仅优化了电荷传输,还通过降低离子扩散能垒,促进了锌离子的快速输运;提升锌负极的循环稳定性;本发明通过对共轭聚合物材料的结构设计,改善传统保护层的离子传导效率低、亲疏水性失衡、保护效果欠佳等缺陷,使锌负极在水系锌离子电池中有更好的离子电导率与更好的亲疏水性能,有利于水系锌离子电池的循环稳定性;
Smart Images

Figure CN122897971A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional polymer materials and aqueous zinc-ion battery technology, and particularly to a conjugated polymer containing naphthalimide units with ethylene glycol side chains, its preparation method and application, and zinc-ion batteries. Background Technology
[0002] The rapid development of smart wearable devices, such as health monitoring systems, flexible displays, smart textiles, and electronic skin, has placed higher demands on the energy storage devices powering them, as these devices become increasingly sophisticated in function and performance. The power source for wearable devices not only needs high energy density and stable electrochemical performance but also excellent mechanical flexibility, capable of withstanding bending, folding, and twisting deformations without affecting its safety and reliability. Among various energy storage battery systems, aqueous zinc batteries have become one of the ideal power sources for wearable devices due to their advantages such as low cost, high safety, high theoretical capacity, and environmental friendliness. However, long-standing problems with the zinc anode of aqueous zinc batteries, such as dendrite formation, zinc anode corrosion, hydrogen evolution side reactions, and surface passivation, significantly reduce their actual electrochemical performance and stability, thus severely restricting their development and application in wearable and other fields.
[0003] To improve the cycle stability of zinc anodes, existing strategies mainly include the construction of interfacial protective layers, optimization of electrolyte composition, and functionalized separator design. Among these, the strategy of constructing interfacial protective layers has broad application prospects due to its simplicity and direct effects. Its core is to build a stable protective layer material on the surface of the zinc anode, avoiding direct contact between the electrode and the electrolyte, thereby suppressing side reactions and dendrite growth of the zinc anode. Conjugated polymers possess excellent electronic conductivity, chemical stability, and mechanical flexibility, making them promising candidates for use as surface protective layer materials for zinc anodes. However, traditional conjugated polymers exhibit significant hydrophobic properties and weak ion conductivity, resulting in suboptimal protective effects. Therefore, developing novel multifunctional conjugated polymer protective layers that combine high zinc ion conductivity, suitable electronic conductivity, ideal zinc-hydrophilic interface characteristics, excellent chemical stability, and good mechanical flexibility can significantly improve the cycle stability of aqueous zinc batteries, especially their long-term cycle stability under high discharge depth and long-term efficiency, driving technological iteration and industrial application of this type of battery. Summary of the Invention
[0004] This invention addresses the problems of low ion conductivity, hydrophilicity-hydrophobicity imbalance, and poor protective effect in existing aqueous zinc-ion battery anode protective layers, which make it difficult for zinc anodes to achieve long-term cycle stability. Therefore, this invention designs a type of conjugated polymer with naphthimide units and thiophene or thiazole as the molecular backbone, i.e., entirely composed of π units linked by single bonds, with polar ethylene glycol short chains as side chains. The preparation method of the conjugated polymer provided by this invention involves dissolving a naphthimide dibromo monomer with ethylene glycol side chains, a bis(trialkyltin) monomer, a palladium catalyst, a copper catalyst, and ligands in an organic solvent under an inert atmosphere. The reaction system is then subjected to Stille polymerization under light-shielded and reflux conditions to obtain a conjugated polymer containing ethylene glycol side chains of naphthimide units. This conjugated polymer containing ethylene glycol side chains of naphthimide units can be used as a protective layer for the zinc anode of aqueous zinc-ion batteries.
[0005] To achieve the above objectives, the present invention adopts the following technical solution:
[0006] In a first aspect, the present invention provides a conjugated polymer of a naphthalimide unit containing an ethylene glycol side chain, wherein the conjugated polymer has a naphthalimide unit and a thiophene or thiazole as the main molecular chain and a short chain of polar ethylene glycol as the side chain.
[0007] The structural formula of the conjugated polymer is shown below:
[0008] ;
[0009] Where n is an integer from 2 to 1000, and m is an integer from 2 to 10;
[0010] Ar can be any of the following substituents:
[0011] , , , , , , , .
[0012] Secondly, the present invention also provides a method for preparing the conjugated polymer containing naphthalimide units with ethylene glycol side chains, comprising the following steps:
[0013] Under an inert atmosphere, dibromo monomers, bis(trialkyltin) monomers, palladium catalysts, copper catalysts, and ligands are dissolved in an organic solvent and subjected to Stille polymerization under light-protected and reflux conditions to obtain a conjugated polymer containing naphthalimide units with ethylene glycol side chains.
[0014] Thirdly, the present invention also provides the application of the conjugated polymer containing naphthalimide units with ethylene glycol side chains as a negative electrode protective layer for aqueous zinc-ion batteries.
[0015] Fourthly, the present invention also provides a zinc-ion battery negative electrode sheet, comprising a negative electrode and a protective layer located on the surface of the negative electrode, wherein the material of the protective layer is the conjugated polymer containing naphthalimide units with ethylene glycol side chains.
[0016] Fifthly, the present invention also provides a method for preparing the negative electrode sheet of the zinc-ion battery, comprising the following steps: dissolving a conjugated polymer containing naphthalimide units with ethylene glycol side chains in a solvent to prepare a solution, coating the solution onto the surface of the negative electrode, and forming a protective layer on the surface of the negative electrode;
[0017] The solvent includes at least one of chloroform, hexafluoroisopropanol, and chlorobenzene;
[0018] The concentration of the conjugated polymer containing naphthalimide units with ethylene glycol side chains in the solution is 1~10 mg / mL.
[0019] In a sixth aspect, the present invention also provides a zinc-ion battery, including the zinc-ion battery negative electrode sheet.
[0020] The conjugated polymer containing ethylene glycol side chain naphthimide units, its preparation method, and its application, according to the present invention, have the following advantages over the prior art:
[0021] 1. The conjugated polymer of naphthalimide units containing ethylene glycol side chains of the present invention has naphthalimide units and thiophene or thiazole as the molecular backbone, that is, it is entirely composed of π units connected by single bonds. The side chains are short polar ethylene glycol chains. The main chain of the conjugated polymer endows it with hydrophobic properties, which can effectively isolate the zinc anode from direct contact with water molecules, thereby inhibiting side reactions such as hydrogen evolution corrosion; its oligomeric ethylene glycol side chains endow the material with zinc affinity, which not only promotes the growth of zinc but also... 2+ This facilitates the conduction of Zn while simultaneously balancing the hydrophobic effect of the main chain, giving the interface layer a dual function of both zinc affinity and hydrophobicity. The zinc-affinity ethylene glycol segment accelerates the conduction of Zn. 2+ The migration of [Zn(H2O)6] occurs, while the hydrophobic backbone carries [Zn(H2O)6]. 2+ Water molecules in the membrane are blocked from entering, thus significantly promoting the growth of Zn. 2+The desolvation process. The conjugated electronic structure formed by the conjugated backbone of the polymer endows it with appropriate electronic conductivity, thereby effectively regulating the electric field distribution at the electrode / electrolyte interface; this characteristic not only optimizes charge transport, but also promotes the rapid transport of zinc ions by reducing the ion diffusion barrier; thus improving the cycle stability of the zinc anode; this invention improves the defects of traditional protective layers such as low ion conduction efficiency, hydrophilicity-hydrophobicity imbalance, and poor protective effect through structural design of conjugated polymer materials, so that the zinc anode has better ion conductivity and better hydrophilicity-hydrophobicity performance in aqueous zinc-ion batteries, which is beneficial to the cycle stability of aqueous zinc-ion batteries;
[0022] 2. The conjugated polymer provided by this invention is obtained by Stille polymerization of a dibromo monomer and a bis(trialkyltin) monomer. The dibromo monomer is a naphthalimide dibromo monomer containing an ethylene glycol side chain, that is, 2,7-naphthalimide reacts with the bis(trialkyltin) monomer as the main component. The presence of the ethylene glycol side chain makes the conjugated polymer have faster zinc ion affinity and enhances the ionic conductivity of the coating. The naphthalimide conjugated polymer containing an ethylene glycol side chain provided by this invention has a simple chemical structure of the constituent units of the polymer chain, which is beneficial to the large-scale synthesis of aqueous zinc-ion battery negative electrode protective layer materials.
[0023] 3. The conjugated polymer provided by this invention has good solubility in organic solvents such as chloroform and hexafluoroisopropanol, and also has excellent film-forming properties. Tests have shown that when the conjugated polymer provided by this invention is applied to the zinc anode protective layer of an aqueous zinc-ion battery, the aqueous zinc battery exhibits good cycle stability with a cycle life exceeding 3000 hours, demonstrating excellent cycle stability. Attached Figure Description
[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0025] Figure 1 The NMR spectrum of the conjugated polymer PNDI7O-2Th in Example 6 is shown.
[0026] Figure 2 Gel permeation chromatography of the conjugated polymer PNDI7O-2Th in Example 6;
[0027] Figure 3 Thermogravimetric curve of the conjugated polymer PNDI7O-2Th in Example 6;
[0028] Figure 4The NMR spectrum of the conjugated polymer PNDI7O-2Tz in Example 24;
[0029] Figure 5 Gel permeation chromatography of the conjugated polymer PNDI7O-2Tz in Example 24;
[0030] Figure 6 Thermogravimetric curve of the conjugated polymer PNDI7O-2Tz in Example 24;
[0031] Figure 7 For different zinc-zinc symmetric cells at 1 mA cm -2 Charge-discharge test results under the specified conditions;
[0032] Figure 8 The results of charge-discharge tests on different zinc-zinc symmetric batteries under high DOD (68.3%) conditions are presented. Detailed Implementation
[0033] The present invention will now be clearly and completely described with reference to specific embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0034] This invention provides a conjugated polymer containing naphthalimide units with ethylene glycol side chains. The conjugated polymer has naphthalimide units and thiophene or thiazole as the main molecular chain, and the side chains are short-chain polar ethylene glycol. The structural formula of the conjugated polymer is shown below:
[0035] ;
[0036] Wherein, n is a positive integer between 2 and 1000 (inclusive of endpoints 2 and 1000), m is a positive integer between 2 and 10 (inclusive of endpoints 2 and 10), and preferably m is a positive integer between 3 and 9;
[0037] Ar can be any of the following substituents:
[0038] , , , , , , , .
[0039] In some embodiments, the conjugated polymer is selected from any one of the compounds shown in the following structural formulas 1 to 24:
[0040] , , , , , ,
[0041] , , , , , , , , , , , , , , , , , .
[0042] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned conjugated polymer containing naphthalimide units with ethylene glycol side chains, comprising the following steps:
[0043] Under an inert atmosphere, dibromo monomers, bistrialkyltin monomers, palladium catalysts, copper catalysts and ligands were dissolved in an organic solvent and subjected to Stille polymerization under light-protected and reflux conditions. After the reaction was completed, the obtained polymer was extracted and purified to obtain a conjugated polymer containing naphthalimide units with ethylene glycol side chains.
[0044] The structural formula of the dibromo monomer is:
[0045]
[0046] Where m is a positive integer between 2 and 10;
[0047] The structural formula of the bis(trialkyltin) monomer is any one of the following:
[0048] , , , ... , , .
[0049] Specifically, Stille polymerization is a palladium-catalyzed condensation reaction in which organotin bifunctional monomers and aryl dihalogen monomers undergo cross-coupling to continuously build carbon-carbon bonds and synthesize conjugated polymers.
[0050] In some embodiments, the organic solvent is an aromatic solvent, which may be chlorobenzene;
[0051] The palladium catalyst is tris(dibenzylacetone)dipalladium (abbreviated as Pd2(dba)3);
[0052] The copper catalyst is cuprous iodide (CuI);
[0053] The ligand is tris(o-methylphenyl)phosphine (abbreviated as P(o-tol)3).
[0054] In some embodiments, the molar ratio of dibromo monomer, ditrialkyltin monomer, palladium catalyst, copper catalyst, and ligand is 1:1:(0.01~0.05):(0.01~0.05):(0.04~0.2);
[0055] The concentration of dibromo monomer in the organic solvent is 0.005~0.1 mmol / L;
[0056] The reaction temperature for Stille polymerization is 110~130 ℃, and the reaction time is 1~96 h, more preferably 16~72 h.
[0057] In some embodiments, the molar ratio of the dibromo monomer, the ditrialkyltin monomer, the palladium catalyst, the copper catalyst, and the ligand is 1:1:0.02:0.02:0.08;
[0058] The concentration of dibromo monomer in the organic solvent is 0.02~0.06 mmol / L.
[0059] Based on the same inventive concept, the present invention also provides the application of the above-mentioned conjugated polymer containing naphthalimide units with ethylene glycol side chains as a negative electrode protective layer for aqueous zinc-ion batteries.
[0060] Based on the same inventive concept, the present invention also provides a zinc-ion battery negative electrode sheet, including a negative electrode and a protective layer located on the surface of the negative electrode, wherein the material of the protective layer is the above-mentioned conjugated polymer containing naphthalimide units with ethylene glycol side chains.
[0061] Specifically, the negative electrode is a zinc sheet with a thickness of 10~1000 μm, and the protective layer has a thickness of 1~200 μm.
[0062] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned zinc-ion battery negative electrode sheet, comprising the following steps: dissolving a conjugated polymer containing naphthalimide units with ethylene glycol side chains in a solvent to prepare a solution, coating the solution onto the negative electrode surface, and forming a protective layer on the negative electrode surface;
[0063] Solvents include at least one of chloroform, hexafluoroisopropanol, and chlorobenzene;
[0064] The concentration of the conjugated polymer containing naphthalimide units with ethylene glycol side chains in the solution is 1~10 mg / mL;
[0065] The coating method can be spin coating, drip coating, or blade coating;
[0066] Specifically, the solution is coated onto the surface of the negative electrode and heated at 60-80°C for 30-40 minutes to form a protective layer on the surface of the negative electrode.
[0067] Based on the same inventive concept, the present invention also provides a zinc-ion battery, including the aforementioned zinc-ion battery negative electrode sheet, an aqueous electrolyte solution, a separator, and a positive electrode material; such as Na2V6O. 16 (NVO) positive electrode, the electrolyte solution is zinc trifluoromethanesulfonate or zinc sulfate aqueous solution, the electrolyte solution concentration is 2 mol / L, and the diaphragm can be glass fiber diaphragm, polypropylene non-woven fabric diaphragm, etc.
[0068] This invention improves upon the shortcomings of traditional organic coatings, such as low ion conduction efficiency, imbalance of hydrophilicity and hydrophobicity, and poor protective effect, through structural design of conjugated polymer materials. This results in materials with better ion conductivity and better hydrophilicity and hydrophobicity in aqueous zinc-ion batteries, which is beneficial to the cycle stability of aqueous zinc-ion batteries.
[0069] The conjugated polymer provided by this invention is obtained by Stille polymerization of a dibromo monomer and a bis(trialkyltin) monomer. The dibromo monomer is a naphthalimide dibromo monomer containing an ethylene glycol side chain, that is, 2,7-naphthalimide reacts with the bis(trialkyltin) monomer as the main component. The presence of the ethylene glycol side chain makes the conjugated polymer have faster zinc ion affinity and enhances the ionic conductivity of the coating. The naphthalimide conjugated polymer containing an ethylene glycol side chain provided by this invention has a simple chemical structure of the constituent units of the polymer chain, which is beneficial to the large-scale synthesis of aqueous zinc-ion battery anode coating materials.
[0070] In the structural design of the conjugated polymer provided by this invention, the main chain of the conjugated polymer imparts hydrophobic properties, effectively isolating the zinc anode from direct contact with water molecules, thereby suppressing side reactions such as hydrogen evolution corrosion; its oligomeric polyethylene glycol side chains impart zinc affinity to the material, not only promoting Zn... 2+ This facilitates the conduction of Zn while simultaneously balancing the hydrophobic effect of the main chain, giving the interface layer a dual function of both zinc affinity and hydrophobicity. The zinc-affinity ethylene glycol segment accelerates the conduction of Zn. 2+ The migration of [Zn(H2O)6] occurs, while the hydrophobic backbone carries [Zn(H2O)6]. 2+ Water molecules in the membrane are blocked from entering, thus significantly promoting the growth of Zn. 2+The desolvation process. The conjugated electronic structure formed by the conjugated backbone of the polymer endows it with appropriate electronic conductivity, thereby effectively regulating the electric field distribution at the electrode / electrolyte interface. This characteristic not only optimizes charge transport but also promotes the rapid transport of zinc ions by reducing the ion diffusion barrier, thus improving the cycle stability of the zinc anode. The conjugated polymer provided by this invention has good solubility in organic solvents such as chloroform and hexafluoroisopropanol, and also exhibits excellent film-forming properties. Tests have shown that when the conjugated polymer provided by this invention is applied to the zinc anode protective layer of an aqueous zinc-ion battery, the aqueous zinc battery exhibits good cycle stability, with a cycle life exceeding 3000 h, demonstrating excellent cycle stability.
[0071] The following specific embodiments further illustrate the conjugated polymer containing ethylene glycol side chains of naphthalimide units, its preparation method, applications, and zinc-ion batteries of the present invention. This section further illustrates the content of the present invention with reference to specific embodiments, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods, and equipment used in the present invention are conventional reagents, methods, and equipment in the art.
[0072] The chemical substances involved in the following examples may be represented by their chemical names, such as 2,5-bis(trimethyltinyl)thiophene.
[0073] Example 1
[0074] This embodiment provides a conjugated polymer containing naphthalimide units with ethylene glycol side chains, which is the compound shown in structural formula 1 above: poly(2,7-bis(2,5,8,11,14-pentahexadecane-16-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-thiophene (PNDI5O-T), and its preparation method is as follows:
[0075] (1) Preparation of 4,9-dibromo-2,7-bis(2,5,8,11,14-pentahexadecane-16-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone (NDI-5O) containing ethylene glycol side chains as a dibromo-2-bromo-2-bis(2,5,8,11,14-pentahexadecane-16-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone (NDI-5O)
[0076] The dibromo monomer of naphthalimide containing an ethylene glycol side chain: 4,9-dibromo-2,7-bis(2,5,8,11,14-pentahexadecane-16-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone, has the following chemical reaction formula:
[0077]
[0078] Aminopentaethylene monomethyl ether (215 mg, 0.5 mmol) was added to 10 mL of glacial acetic acid containing a suspension of monomer 1 (252 mg, 1 mmol) of 2,6-dibromo-1,4,5,8-naphthalenetetracarboxylic acid diimide. The mixture was heated at 120 °C for 4 hours. The reaction mixture was then cooled to room temperature, and water (100 mL) was added. The mixture was then extracted with dichloromethane. The organic phase was washed with brine, dried over anhydrous sodium sulfate, and the solvent was removed by rotary evaporation. The crude product was purified by silica gel column chromatography using dichloromethane / acetone as the eluent to give target compound 2 (NDI-5O) (89 mg, 20%) as a bright yellow solid.
[0079] (2) Synthesis of conjugated polymer PNDI5O-T
[0080] The chemical reaction formula is as follows:
[0081]
[0082] Weigh the target compound 2 (NDI-5O) (178 mg, 0.2 mmol), 2,5-bis(trimethyltinyl)thiophene (82 mg, 0.2 mmol), tris(dibenzylacetone)palladium (4 mg, 0.004 mmol), cuprous iodide (4 mg, 0.02 mmol), and tris(o-methylphenyl)phosphine (6 mg, 0.016 mmol) into a nitrogen-filled polymerization tube. Add 5 mL of dry chlorobenzene solvent. Heat the reaction system to 130 °C under reflux in the dark for 24 h. After the reaction is complete, add 5 mL of chloroform to the system. Transfer the reaction solution to 100 mL of methanol and add 1 mL of hydrochloric acid. Filter and collect the solid. Extract the solid sequentially with methanol, n-hexane, acetone, and chloroform using a Soxhlet extractor. Finally, concentrate the chloroform extract, transfer it back to methanol to precipitate, collect it, and place it in a vacuum (≈10 Torr) at room temperature for 24 hours. After drying, PNDI5O-T (140 mg) was obtained.
[0083] Yield 83%.
[0084] The NMR analysis of PNDI5O-T yielded the following results: 1¹H NMR (400 MHz, Chloroform-d) 6.5–9.5 (m, 4H), 5.5–2.8 (m, 48H); Elemental analysis of PNDI5O-T: calculated C 58.81; H 6.42; N 3.43; O 27.42; S 3.92; tested C 58.42; H 6.90; N 3.67; O 27.4; S 3.52; Gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35 ℃) analysis of PNDI5O-T yielded the following results: Mn = 43615, PDI = 1.46, where Mn represents the number-average molecular weight and PDI represents the polydispersity index.
[0085] Example 2
[0086] This embodiment provides a conjugated polymer containing a naphthalimide unit with an ethylene glycol side chain, which is the compound shown in structural formula 2 above: poly(2,7-bis(2,5,8,11,14,17-hexoxyoctadel-19-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-thiophene (PNDI6O-T), and its preparation method is as follows:
[0087] (1) Preparation of 4,9-dibromo-2,7-bis(2,5,8,11,14,17-hexaoxhexadecane-19-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone (NDI-6O) containing ethylene glycol side chains as a dibromo-2-dibromo-2-di(2,5,8,11,14,17-hexaoxhexadecane-19-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone (NDI-6O)
[0088] The synthesis of the naphthalimide dibromomonomer (NDI-6O) differs from that in Example 1 (1) in that the side-chain aminopentaethylene glycol monomethyl ether is replaced with aminohexaethylene glycol monomethyl ether, while the remaining process steps and parameter settings are the same as in Example 1 (1), yielding the naphthalimide dibromomonomer (NDI-6O). 36 H 48 O 14 Br2N2;
[0089] (2) The chemical reaction formula for the synthesis of the conjugated polymer PNDI6O-T is as follows:
[0090]
[0091] The difference between this step and (2) in Example 1 is that the amount of naphthalimide dibromo monomer 3 (NDI-6O) is 194 mg (0.2 mmol), and the remaining process steps and parameter settings are the same as in (2) of Example 1, to obtain the conjugated polymer PNDI6O-T (162 mg, yield 87%).
[0092] Elemental analysis of naphthalimide dibromo monomer 3 (NDI-6O) was performed: theoretical values: C 44.47; H 2.99; Br 29.59; N 5.19; O 17.77; measured values: C 44.44; H 2.98; Br 29.52; N 5.18; O 17.79. NMR analysis of PNDI6O-T yielded the following results: 1 HNMR (400 MHz, Chloroform-d) 6.5-9.5 (m, 4 H), 5.5-2.8 (m, 54H);
[0093] Elemental analysis of PNDI6O-T: calculated values C 58.39; H 6.68; N 3.10; O 28.28; S 3.5; tested values C 58.43; H 5.94; N 6.63; O 28.47; S 3.53. Gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35 ℃) analysis of PNDI6O-T yielded the following results: Mn=42854, PDI=1.53.
[0094] Example 3
[0095] This embodiment provides a conjugated polymer containing a naphthalimide unit with an ethylene glycol side chain, which is the compound shown in structural formula 3 above: poly(2,7-bis(2,5,8,11,14,17,20-heptaoxadocosane-22-yl)benzo[lmn][3,8]phenanthroline 1,3,6,8(2H,7H)tetraone-co-thiophene (PNDI7O-T), and its preparation method is as follows:
[0096] (1) Preparation of 4,9-dibromo-2,7-bis(2,5,8,11,14,17,20-heptaoxadocosane-22-yl)benzo[lmn][3,8]phenanthroline 1,3,6,8(2H,7H)tetraone (NDI-7O):
[0097] The synthesis of naphthalimide dibromomonomer 4 (NDI-7O) differs from that in Example 1 (1) in that the side-chain aminohexaethylene glycol monomethyl ether is replaced with aminoheptaethylene glycol monomethyl ether, while the remaining process steps and parameter settings are the same as in Example 1 (1), yielding naphthalimide dibromomonomer 4 (NDI-7O). 40 H 52 O 16 Br2N2;
[0098] (2) The chemical reaction formula for the synthesis of the conjugated polymer PNDI7O-T is as follows:
[0099]
[0100] The difference between this step and (2) in Example 1 is that the dibromo monomer is naphthalimide dibromo monomer 4 (NDI-7O), and its dosage is 210 mg (0.2 mmol). The remaining process steps and parameter settings are the same as in (2) of Example 1, and the conjugated polymer PNDI7O-T (172 mg, yield 85%) is obtained.
[0101] Elemental analysis of naphthalimide dibromo monomer 4 (NDI-7O) was performed: theoretical values: C 48.44; H 5.42; Br 17.90; N 3.14; O 25.09; measured values: C 48.50; H 5.48; Br 17.94; N 3.11; O 25.10. NMR analysis of PNDI7O-T yielded the following results: 1 HNMR (400 MHz, Chloroform-d) 6.5-9.5 (m, 4 H), 5.5-2.8 (m, 64H);
[0102] Elemental analysis of PNDI7O-T: Calculated values: C 58.05; H 6.90; N 2.82; O 29.00; S 3.23; Analyzed values: C 58.40; H 6.91; N 2.69; O 29.49; S 3.51; Gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35℃) results: Mn=46756, PDI=1.69.
[0103] Example 4
[0104] This embodiment provides a conjugated polymer containing a naphthalimide unit with an ethylene glycol side chain, which is the compound shown in the above structural formula 4: poly(2,7-bis(2,5,8,11,14-pentahexadecane-16-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-thiophene (PNDI5O-2Th).
[0105] The difference between this embodiment and Embodiment 1 is as follows:
[0106] The conjugated polymer is PNDI5O-2Th, and its synthetic formula is as follows:
[0107]
[0108] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to 5,5-bis(trimethyltinyl)-2,2'-bithiophene, i.e., the amount used was 99 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 1, and the conjugated polymer PNDI5O-2Th (161 mg, yield 87%) was obtained.
[0109] The NMR analysis of PNDI5O-2Th yielded the following results: 1 ¹H NMR (400 MHz, Chloroform-d) 6.5–9.5 (m, 6 H), 5.5–2.8 (m, 48 H); Elemental analysis of PNDI₅O₂�Th: calculated values C 58.78; H 6.05; N 3.12; O 24.91; S 7.13; tested values C 59.70; H 6.21; N 3.22; O 24.06; S 7.02; Gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35℃) analysis of PNDI₅O₂�Th: Mn = 45332, PDI = 1.63.
[0110] Example 5
[0111] This embodiment provides a conjugated polymer containing a naphthalimide unit with an ethylene glycol side chain, which is the compound shown in the above structural formula 5: poly(2,7-bis(2,5,8,11,14,17-hexoxyoctade-19-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-thiophene (PNDI6O-2Th).
[0112] The difference between this embodiment and Embodiment 2 is as follows:
[0113] The conjugated polymer is PNDI6O-2Th, and its synthetic formula is as follows:
[0114]
[0115] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to 5,5-bis(trimethyltinyl)-2,2'-bithiophene, i.e., the amount used was 99 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 2, and the conjugated polymer PNDI6O-2Th (164 mg, yield 81%) was obtained.
[0116] The NMR analysis of PNDI6O-2Th yielded the following results: 1 HNMR (400 MHz, Chloroform-d) 6.5-9.5 (m, 6 H), 5.5-2.8 (m, 56 H);
[0117] Elemental analysis of PNDI6O-2Th: calculated values: C 58.40; H 6.33; N 2.84; O 25.93; S 6.50; tested values: C 59.36; H 6.75; N 2.36; O 25.12; S 6.42. Gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35℃) was performed on PNDI6O-2Th, and the results are as follows: Mn=46732, PDI=1.64.
[0118] Example 6
[0119] This embodiment provides a conjugated polymer containing naphthalimide units with ethylene glycol side chains, which is the compound shown in the above structural formula 6: poly(2,7-bis(2,5,8,11,14,17,20-heptaoxadocosane-22-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)tetraketone-co-thiophene (PNDI7O-2Th).
[0120] The difference between this embodiment and Embodiment 3 is as follows:
[0121] The conjugated polymer is PNDI7O-2Th, and its synthetic formula is as follows:
[0122]
[0123] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to 5,5-bis(trimethyltinyl)-2,2'-bithiophene, i.e., the amount used was 99 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 3, and the conjugated polymer PNDI7O-2Th (173 mg, yield 80%) was obtained.
[0124] NMR analysis of PNDI7O-2Th yielded the following results: Figure 1 As shown, its structural characterization is as follows: 1 ¹H NMR (400 MHz, Chloroform-d) 6.5–9.5 (m, 6H), 5.5–2.8 (m, 64H); Elemental analysis of PNDI7O-2Th: calculated values C 58.09, H 6.56; N 2.61; O 26.78; S 5.96; tested values C 58.99; H 6.86; N 2.24; O 26.30; S 5.61; Gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35 °C) was performed on PNDI7O-2Th. The gel permeation chromatography results are as follows: Figure 2 As shown, Mn=39178 ( Figure 2The value of the maximum peak is 66162 (Mn is the number average molecular weight), and PDI = 2.25. Thermogravimetric analysis (TGA) of PNDI7O-2Th was performed (temperature 30~600℃, heating rate 20℃ / min, under nitrogen atmosphere). The thermogravimetric curve is shown below. Figure 3 As shown.
[0125] Example 7
[0126] This embodiment provides a conjugated polymer containing naphthalimide units with ethylene glycol side chains, which is the compound shown in the above structural formula 7: poly2,7-bis(2,5,8,11,14-pentahexadecane-16-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-trithiophene (PNDI5O-3T).
[0127] The difference between this embodiment and Embodiment 1 is as follows:
[0128] The conjugated polymer is PNDI5O-3T, and its synthesis reaction formula is as follows:
[0129]
[0130] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to 5,5''-bis(trimethyltinyl)-2,2':5',2''-terthiophene, and the amount used was 115 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 1, and the conjugated polymer PNDI5O-3T (164 mg, yield 83%) was obtained.
[0131] The NMR analysis of PNDI5O-3T yielded the following results: 1 ¹H NMR (400 MHz, Chloroform-d) 6.5–9.5 (m, 8H), 5.5–2.8 (m, 48H); Elemental analysis of PNDI₅O₃T: Calculated C 58.76; H 5.75; N 2.86; O 22.83; S 9.80; Measured C 58.11; H 5.08; N 3.76; O 22.30; S 9.74;
[0132] Gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35 ℃) was used to analyze PNDI5O-3T. The results are as follows: Mn=67894, PDI=1.64.
[0133] Example 8
[0134] This embodiment provides a conjugated polymer containing a naphthalimide unit with an ethylene glycol side chain, which is the compound shown in structural formula 8 above: poly(2,7-bis(2,5,8,11,14,17-hexyloxyoctade-19-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-trithiophene (PNDI6O-3T):
[0135] The difference between this embodiment and Embodiment 2 is as follows:
[0136] The conjugated polymer is PNDI6O-3T, and its synthesis reaction formula is as follows:
[0137]
[0138] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to 5,5''-bis(trimethyltinyl)-2,2':5',2''-terthiophene, and the amount used was 115 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 2, and the conjugated polymer PNDI6O-3T (175 mg, yield 80%) was obtained.
[0139] The NMR analysis of PNDI6O-3T yielded the following results: 1 ¹H NMR (400 MHz, Chloroform-d) 6.5–9.5 (m, 8 H), 5.5–2.8 (m, 56 H); Elemental analysis of PNDI6O-3T: calculated C 58.41; H 6.03; N 2.62; O 23.94; S 8.99; tested C 58.39; H 6.50; N 2.36; O 23.36; S 8.39; Gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35 ℃) analysis of PNDI6O-3T: Mn=67744, PDI=1.65.
[0140] Example 9
[0141] This embodiment provides a conjugated polymer containing a naphthalimide unit with an ethylene glycol side chain, which is the compound shown in structural formula 9 above: poly(2,7-bis(2,5,8,11,14,17-hexoxyoctade-19-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-trithiophene (PNDI7O-3T):
[0142] The difference between this embodiment and Embodiment 3 is as follows:
[0143] The conjugated polymer is PNDI7O-3T, and its synthesis reaction formula is as follows:
[0144]
[0145] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to 5,5''-bis(trimethyltinyl)-2,2':5',2''-terthiophene, and the dosage was 115 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 3, and the conjugated polymer PNDI7O-3T (187 mg, yield 79%) was obtained.
[0146] The NMR analysis of PNDI7O-3T yielded the following results: 1 ¹H NMR (400 MHz, Chloroform-d) 6.5–9.5 (m, 8H), 5.5–2.8 (m, 64H); Elemental analysis of PNDI₇O₃T: Calculated C 58.12; H 6.27; N 2.42; O 24.88; S 8.31; Measured C 58.60; H 6.85; N 3.02; O 23.99; S 7.55;
[0147] Gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35 ℃) was used to analyze PNDI7O-3T. The results are as follows: Mn=71253, PDI=1.77.
[0148] Example 10
[0149] This embodiment provides a conjugated polymer containing a naphthalimide unit with an ethylene glycol side chain, which is the compound shown in structural formula 10 above: poly(2,7-bis(2,5,8,11,14-pentahexadecane-16-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-thiophene (PNDI5O-TT):
[0150] The difference between this embodiment and Embodiment 1 is as follows:
[0151] The conjugated polymer is PNDI5O-TT, and its synthesis reaction formula is as follows:
[0152]
[0153] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to 2,5-bis(trimethyltinyl)thiophene[3,2-b]thiophene, and the amount used was 93 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 1, and the conjugated polymer PNDI5O-TT (147 mg, yield 82%) was obtained.
[0154] The NMR analysis of PNDI5O-TT yielded the following results: 1 ¹H NMR (400 MHz, Chloroform-d) 6.5–9.5 (m, 4H), 5.5–2.8 (m, 48H); Elemental analysis of PNDI₅O-TT: Calculated C 57.79; H 6.00; N 3.21; O 25.66; S 7.34; Measured C 57.61; H 6.33; N 3.46; O 25.27; S 7.30;
[0155] Gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35 ℃) was used to analyze PNDI5O-TT. The results are as follows: Mn=28581, PDI=1.53.
[0156] Example 11
[0157] This embodiment provides a conjugated polymer containing a naphthalimide unit with an ethylene glycol side chain, which is the compound shown in structural formula 11 above: poly(2,7-bis(2,5,8,11,14,17-hexoxyoctade-19-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-thiophene (PNDI6O-TT):
[0158] The difference between this embodiment and Embodiment 2 is as follows:
[0159] The conjugated polymer is PNDI6O-TT, and its synthesis reaction formula is as follows:
[0160]
[0161] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to 2,5-bis(trimethyltinyl)thiophene[3,2-b]thiophene, and the amount used was 93 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 2, and the conjugated polymer PNDI6O-TT (162 mg, yield 82%) was obtained.
[0162] The NMR analysis of PNDI6O-TT yielded the following results: 1 ¹H NMR (400 MHz, Chloroform-d) 6.5–9.5 (m, 4H), 5.5–2.8 (m, 56H); Elemental analysis of PNDI₆O-TT: calculated C 57.49; H 6.29; N 2.91; O 26.63; S 6.67; tested C 57.22; H 5.79; N 2.92; O 26.22; S 7.82;
[0163] Gel permeation spectroscopy (GPC, hexafluoroisopropanol, polystyrene as standard, 35 ℃) was performed on PNDI6O-TT, and the results are as follows: Mn=28646, PDI=1.86.
[0164] Example 12
[0165] This embodiment provides a conjugated polymer containing a naphthalimide unit with an ethylene glycol side chain, which is the compound shown in structural formula 12 above: poly(2,7-bis(2,5,8,11,14,17-hexoxyoctade-19-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-thiophene (PNDI7O-TT):
[0166] The difference between this embodiment and Embodiment 3 is as follows:
[0167] The conjugated polymer is PNDI7O-TT, and its synthesis reaction formula is as follows:
[0168]
[0169] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to 2,5-bis(trimethyltinyl)thiophene[3,2-b]thiophene, and the amount used was 93 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 3, and the conjugated polymer PNDI7O-TT (165 mg, yield 77%) was obtained.
[0170] The NMR analysis of PNDI7O-TT yielded the following results: 1 ¹H NMR (400 MHz, Chloroform-d) 6.5–9.5 (m, ⁴ H), 5.5–2.8 (m, ⁶⁴ H); Elemental analysis of PNDI₇O-TT: calculated C 57.24; H 6.53; N 2.67; O 27.45; S 6.11; tested values: C 57.70; H 6.15; N 2.45; O 27.80; S 6.90.
[0171] Gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35 ℃) was used to analyze PNDI7O-TT. The results are as follows: Mn=31254, PDI=1.79.
[0172] Example 13
[0173] This embodiment provides a conjugated polymer containing a naphthalimide unit with an ethylene glycol side chain, which is the compound shown in the above structural formula 13: poly(2,7-bis(2,5,8,11,14-pentahexadecane-16-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-dithiophene-thiophene (PNDI5O-TTT).
[0174] The difference between this embodiment and Embodiment 1 is as follows:
[0175] The conjugated polymer is PNDI5O-TTT, and its synthesis reaction formula is as follows:
[0176]
[0177] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to 2,6-bis(trimethyltinyl)dithiophene[3,2-b]thiophene, and the amount used was 104 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 1, and the conjugated polymer PNDI5O-TTT (151 mg, yield 79%) was obtained.
[0178] The NMR analysis of PNDI5O-TTT yielded the following results: 1 ¹H NMR (400 MHz, Chloroform-d) 6.5–9.5 (m, 4H), 5.5–2.8 (m, 48H); Elemental analysis of PNDI₅O-TTT: Calculated values: C 56.88; H 5.64; N 3.02; O 24.11; S 10.35; Measured values: C 56.0; H 5.8; N 3.0; O 24.6; S 10.37;
[0179] Gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35 ℃) was used to analyze PNDI5O-TTT. The results are as follows: Mn=45289, PDI=1.81.
[0180] Example 14
[0181] This embodiment provides a conjugated polymer containing a naphthalimide unit with an ethylene glycol side chain, which is the compound shown in structural formula 14 above: poly(2,7-bis(2,5,8,11,14,17-hexyloxyoctade-19-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-dithiophene-thiophene (PNDI6O-TTT):
[0182] The difference between this embodiment and Embodiment 2 is as follows:
[0183] The conjugated polymer is PNDI6O-TTT, and its synthesis reaction formula is as follows:
[0184]
[0185] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to 2,6-bis(trimethyltinyl)dithiophene[3,2-b]thiophene, and the amount used was 104 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 2, and the conjugated polymer PNDI6O-TTT (152 mg, yield 73%) was obtained.
[0186] The NMR analysis of PNDI6O-TTT yielded the following results: 1 ¹H NMR (400 MHz, Chloroform-d) 6.5–9.5 (m, 4H), 5.5–2.8 (m, 56H); Elemental analysis of PNDI₆O-TTT: Calculated values: C 56.68; H 5.95; N 2.75; O 25.17; S 9.46; Measured values: C 56.70; H 5.35; N 2.63; O 25.25; S 9.25;
[0187] Gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35 ℃) was used to analyze PNDI6O-TTT. The results are as follows: Mn=64351, PDI=9.96.
[0188] Example 15
[0189] This embodiment provides a conjugated polymer containing a naphthalimide unit with an ethylene glycol side chain, which is the compound shown in structural formula 15 above: poly(2,7-bis(2,5,8,11,14,17-hexoxyoctade-19-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-dithiophene-thiophene (PNDI7O-TTT):
[0190] The difference between this embodiment and Embodiment 3 is as follows:
[0191] The conjugated polymer is PNDI7O-TTT, and its synthesis reaction formula is as follows:
[0192]
[0193] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to 2,6-bis(trimethyltinyl)dithiophene[3,2-b]thiophene, and the amount used was 104 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 3, and the conjugated polymer PNDI7O-TTT (165 mg, yield 73%) was obtained.
[0194] The NMR analysis of PNDI7O-TTT yielded the following results: 1 ¹H NMR (400 MHz, Chloroform-d) 6.5–9.5 (m, ⁴ H), 5.5–2.8 (m, ⁶⁴ H); Elemental analysis of PNDI₇O-TTT: Calculated values: C 56.51; H 6.20; N 2.53; O 26.05; S 8.70; Measured values: C 55.22; H 6.72; N 3.23; O 26.22; S 8.61;
[0195] Gel permeation spectroscopy (GPC, hexafluoroisopropanol, polystyrene as standard, 35 ℃) was performed on PNDI7O-TTT, and the results are as follows: Mn=72134, PDI=1.93.
[0196] Example 16
[0197] This embodiment provides a conjugated polymer containing a naphthalimide unit with an ethylene glycol side chain, which is the compound shown in structural formula 16 above: poly(2,7-bis(2,5,8,11,14-pentahexadecane-16-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-(E)-1,2-(dithiophene-2-yl)ethylene (PNDI5O-TvT):
[0198] The difference between this embodiment and Embodiment 1 is as follows:
[0199] The conjugated polymer is PNDI5O-TvT, and its synthesis reaction formula is as follows:
[0200]
[0201] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to (E)-1,2-bis(5-trimethyltinyl)thiophene-2-yl-ethylene, and the amount used was 104 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 1, and the conjugated polymer PNDI5O-TvT (139 mg, yield 73%) was obtained.
[0202] The NMR analysis of PNDI5O-TvT yielded the following results: 1¹H NMR (400 MHz, Chloroform-d) 6.5–9.5 (m, 8 H), 5.5–2.8 (m, 48 H); Elemental analysis of PNDI₅O-TvT: Calculated C 59.73; H 6.10; N 3.03; O 24.21; S 6.93; Measured C 58.87; H 6.51; N 3.12; O 24.72; S 6.78;
[0203] Gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35 ℃) was used to analyze PNDI5O-TvT. The results are as follows: Mn=58416, PDI=1.84.
[0204] Example 17
[0205] This embodiment provides a conjugated polymer containing a naphthalimide unit with an ethylene glycol side chain, which is the compound shown in structural formula 17 above: poly(2,7-bis(2,5,8,11,14,17-hexoxyoctade-19-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-(E)-1,2-(dithiophene-2-yl)ethylene (PNDI6O-TvT):
[0206] The difference between this embodiment and Embodiment 2 is as follows:
[0207] The conjugated polymer is PNDI6O-TvT, and its synthesis reaction formula is as follows:
[0208]
[0209] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to (E)-1,2-bis(5-trimethyltinyl)thiophene-2-yl-ethylene, and the amount used was 104 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 2, and the conjugated polymer PNDI6O-TvT (162 mg, yield 78%) was obtained.
[0210] The NMR analysis of PNDI6O-TvT yielded the following results: 1 ¹H NMR (400 MHz, Chloroform-d) 6.5–9.5 (m, 8 H), 5.5–2.8 (m, 56 H); Elemental analysis of PNDI₆O-TvT: calculated C 59.27; H 6.37; N 2.76; O 25.27; S 6.33; tested C 59.10; H 5.88; N 3.65; O 25.77; S 6.59;
[0211] Gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35 ℃) was used to analyze PNDI6O-TvT. The results are as follows: Mn=58469, PDI=1.69.
[0212] Example 18
[0213] This embodiment provides a conjugated polymer containing a naphthalimide unit with an ethylene glycol side chain, which is the compound shown in structural formula 18 above: poly(2,7-bis(2,5,8,11,14,17-hexyloxyoctade-19-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-(E)-1,2-bis(thiophene-2-yl)ethylene (PNDI7O-TvT):
[0214] The difference between this embodiment and Embodiment 3 is as follows:
[0215] The conjugated polymer is PNDI7O-TvT, and its synthesis reaction formula is as follows:
[0216]
[0217] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to (E)-1,2-bis(5-trimethyltinyl)thiophene-2-yl-ethylene, and the amount used was 104 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 2, and the conjugated polymer PNDI7O-TvT (176 mg, yield 78%) was obtained.
[0218] The NMR analysis of PNDI7O-TvT yielded the following results: 1 ¹H NMR (400 MHz, Chloroform-d) 6.5–9.5 (m, 8H), 5.5–2.8 (m, 64H); Elemental analysis of PNDI₇O-TvT: Calculated C 58.89; H 6.59; N 2.54; O 26.15; S 5.82; Measured C 58.23; H 6.24; N 3.28; O 26.37; S 5.89;
[0219] Gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35 ℃) was used to analyze PNDI7O-TvT. The results are as follows: Mn=62844, PDI=1.72.
[0220] Example 19
[0221] This embodiment provides a conjugated polymer containing a naphthaleneimide unit with an ethylene glycol side chain, which is the compound shown in structural formula 19 above: poly(2,7-bis(2,5,8,11,14-pentahexadecane-16-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-3,3'-difluoro-5,5'-bithiophene (PNDI5O-2T2F-3):
[0222] The difference between this embodiment and Embodiment 1 is as follows:
[0223] The conjugated polymer is PNDI5O-2T2F-3, and its synthesis reaction formula is as follows:
[0224]
[0225] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to 3,3'-difluoro-bis(trimethyltinane)-5,5'-bithiophene, and the amount used was 106 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 1, and the conjugated polymer PNDI5O-2T2F-3 (138 mg, yield 73%) was obtained.
[0226] The NMR analysis of PNDI5O-2T2F-3 yielded the following results: 1 HNMR (400 MHz, Chloroform-d) 6.5-9.5 (m, 4 H), 5.5-2.8 (m, 48 H);
[0227] Elemental analysis was performed on PNDI5O-2T2F-3; calculated values: C 56.52; H 5.61; F 4.06; N 3.00; O 23.96; S 6.86; tested values: C 55.52; H 5.51; F 4.56; N 3.25; O 23.84; S 7.16. Gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35 ℃) was performed on PNDI5O-2T2F-3, and the results are as follows: Mn=52743, PDI=1.73.
[0228] Example 20
[0229] This embodiment provides a conjugated polymer containing a naphthaleneimide unit with an ethylene glycol side chain, which is the compound shown in the above structural formula 20: poly(2,7-bis(2,5,8,11,14,17-hexyloxyoctade-19-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-3,3'-difluoro-5,5'-bithiophene (PNDI6O-2T2F-3):
[0230] The difference between this embodiment and Embodiment 2 is as follows:
[0231] The conjugated polymer is PNDI6O-2T2F-3, and its synthesis reaction formula is as follows:
[0232]
[0233] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to 3,3'-difluoro-bis(trimethyltinane)-5,5'-bithiophene, and the amount used was 106 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 2, and the conjugated polymer PNDI6O-2T2F-3 (157 mg, yield 76%) was obtained.
[0234] The NMR analysis of PNDI6O-2T2F-3 yielded the following results: 1 HNMR (400 MHz, Chloroform-d) 6.5-9.5 (m, 4 H), 5.5-2.8 (m, 56 H);
[0235] Elemental analysis was performed on PNDI6O-2T2F-3; calculated values: C 56.35; H 5.91; F 3.71; N 2.74; O 25.02; S 6.27; tested values: C 55.35; H 6.41; F 3.75; N 2.75; O 25.22; S 6.13. Gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35 ℃) was performed on PNDI6O-2T2F-3, and the results are as follows: Mn=48691, PDI=1.83.
[0236] Example 21
[0237] This embodiment provides a conjugated polymer containing a naphthalimide unit with an ethylene glycol side chain, which is the compound shown in structural formula 21 above: poly(2,7-bis(2,5,8,11,14,17-hexyloxyoctadel-19-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-3,3'-difluoro-5,5'-bithiophene (PNDI7O-2T2F-3):
[0238] The difference between this embodiment and Embodiment 3 is as follows:
[0239] The conjugated polymer is PNDI7O-2T2F-3, and its synthesis reaction formula is as follows:
[0240]
[0241] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to 3,3'-difluoro-bis(trimethyltinane)-5,5'-bithiophene, and the amount used was 106 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 3, and the conjugated polymer PNDI7O-2T2F-3 (182 mg, yield 81%) was obtained.
[0242] The NMR analysis of PNDI7O-2T2F-3 yielded the following results: 1 HNMR (400 MHz, Chloroform-d) 6.5-9.5 (m, 4 H), 5.5-2.8 (m, 64 H);
[0243] Elemental analysis was performed on PNDI7O-2T2F-3; calculated values: C 56.21; H 6.17; F 3.42; N 2.52; O 25.92; S 5.77; tested values: C 58.73; H 6.55; F 3.58; N 2.55; O 25.54; S 2.95. Gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35 ℃) was performed on PNDI7O-2T2F-3, and the results are as follows: Mn=48691, PDI=1.83.
[0244] Example 22
[0245] This embodiment provides a conjugated polymer containing a naphthalimide unit with an ethylene glycol side chain, which is the compound shown in structural formula 22 above: poly(2,7-bis(2,5,8,11,14-pentahexadecane-16-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-5,5'-bithiazole (PNDI5O-2Tz):
[0246] The difference between this embodiment and Embodiment 1 is as follows:
[0247] The conjugated polymer is PNDI5O-2Tz, and its synthesis reaction formula is as follows:
[0248]
[0249] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to 3,3'-bis(trimethyltinyl)-5,5'-bithiazole, and the dosage was 99 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 1, and the conjugated polymer PNDI5O-2Tz (146 mg, yield 79%) was obtained.
[0250] The NMR analysis of PNDI5O-2Tz yielded the following results: 1¹H NMR (400 MHz, Chloroform-d) 6.5–9.5 (m, 4H), 5.5–2.8 (m, 48H); Elemental analysis of PNDI₅O₂Tz: Calculated C 55.99; H 5.82; N 6.22; O 24.86; S 7.12; Measured C 55.10; H 6.05; N 6.72; O 23.07; S 7.27;
[0251] The results of gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35 °C) analysis of PNDI5O-2Tz were as follows: Mn=46461, PDI=1.71.
[0252] Example 23
[0253] This embodiment provides a conjugated polymer containing a naphthalimide unit with an ethylene glycol side chain, which is the compound shown in structural formula 23 above: poly(2,7-bis(2,5,8,11,14,17-hexyloxyoctadel-19-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-5,5'-bithiazole (PNDI6O-2Tz):
[0254] The difference between this embodiment and Embodiment 2 is as follows:
[0255] The conjugated polymer is PNDI6O-2Tz, and its synthesis reaction formula is as follows:
[0256]
[0257] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to 3,3'-bis(trimethyltinyl)-5,5'-bithiazole, and the amount used was 99 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 2, and the conjugated polymer PNDI6O-2Tz (156 mg, yield 77%) was obtained.
[0258] The NMR analysis of PNDI6O-2Tz yielded the following results: 1 ¹H NMR (400 MHz, Chloroform-d) 6.5–9.5 (m, 4H), 5.5–2.8 (m, 56H); Elemental analysis of PNDI₆O₂Tz: Calculated C 55.86; H 6.11; N 5.66; O 25.88; S 6.48; Measured C 55.64; H 6.16; N 5.71; O 25.55; S 6.55;
[0259] Gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35 ℃) was used to analyze PNDI6O-2Tz. The results are as follows: Mn=48966, PDI=1.67.
[0260] Example 24
[0261] This embodiment provides a conjugated polymer containing a naphthalimide unit with an ethylene glycol side chain, which is the compound shown in structural formula 24 above: poly(2,7-bis(2,5,8,11,14,17-hexyloxyoctade-19-yl)benzo[lmn][3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone-co-5,5'-bithiazole (PNDI7O-2Tz):
[0262] The difference between this embodiment and Embodiment 3 is as follows:
[0263] The conjugated polymer is PNDI7O-2Tz, and its synthesis reaction formula is as follows:
[0264]
[0265] In this process, the bis(trimethyltin) monomer was changed from 2,5-bis(trimethyltinyl)thiophene to 3,3'-bis(trimethyltinyl)-5,5'-bithiazole, and the amount used was 99 mg (0.2 mmol). The remaining process steps and parameter settings were the same as in Example 3, and the conjugated polymer PNDI7O-2Tz (157 mg, yield 72%) was obtained.
[0266] NMR analysis of PNDI7O-2Tz yielded the following results: Figure 4 As shown, its structural characterization is as follows: 1 ¹H NMR (400 MHz, Chloroform-d) 6.5–9.5 (m, ⁴ H), 5.5–2.8 (m, ⁶⁴ H); elemental analysis of PNDI₇O₂Tz: calculated C 55.75; H 6.36; N 5.20; O 26.73; S 5.95; measured C 55.45; H 6.26; N 5.21; O 26.63; S 5.85;
[0267] PNDI7O-2Tz was analyzed by gel permeation chromatography (GPC, hexafluoroisopropanol, polystyrene as standard, 35 °C). The gel permeation chromatography results are as follows: Figure 5 As shown, Mn=28578 ( Figure 5 The value of the maximum peak is 58847 (Mn is the number average molecular weight), and PDI = 3.20.
[0268] Thermogravimetric analysis (TGA) was performed on PNDI7O-2Tz, and the thermogravimetric curve is shown below. Figure 6As shown. Conjugated polymer structure and thermal property testing.
[0269] Figure 1 The NMR spectrum of the conjugated polymer PNDI7O-2Th in Example 6 is shown.
[0270] Figure 2 Gel permeation chromatography of the conjugated polymer PNDI7O-2Th in Example 6;
[0271] Figure 3 Thermogravimetric curve of the conjugated polymer PNDI7O-2Th in Example 6;
[0272] Figure 4 The NMR spectrum of the conjugated polymer PNDI7O-2Tz in Example 24;
[0273] Figure 5 Gel permeation chromatography of the conjugated polymer PNDI7O-2Tz in Example 24;
[0274] Figure 6 Thermogravimetric curve of the conjugated polymer PNDI7O-2Tz in Example 24;
[0275] Specifically, the conjugated polymers PNDI7O-2Th in Example 6 and PNDI7O-2Tz in Example 24 were tested by 1H NMR spectroscopy, gel permeation chromatography and thermogravimetric analysis to confirm their molecular structure, molecular weight and distribution and thermal stability. Figure 1 and Figure 4 The molecular structures of the conjugated polymers PNDI7O-2Th and PNDI7O-2Tz were confirmed. Figure 2 and Figure 5 Gel permeation chromatography of the conjugated polymers PNDI7O-2Th and PNDI7O-2Tz, respectively. Figure 3 , 6 The results show the thermal stability of the conjugated polymers PNDI7O-2Th and PNDI7O-2Tz, indicating that PNDI7O-2Th and PNDI7O-2Tz can remain stable and undegraded after being baked at 80 °C for 30 min.
[0276] Electrical performance testing
[0277] The conjugated polymers PNDI7O-2Th from Example 6 and PNDI7O-2Tz from Example 24 were dissolved in chloroform to form a solution with a concentration of 5 mg / mL. This solution was then dropped onto a zinc sheet and baked at 80 °C for 30 min to form a protective layer with a thickness of 1 μm, thus obtaining the negative electrode sheet. The negative electrode sheet was assembled into a zinc-zinc symmetrical battery, wherein the electrolyte solution was a 2 mol / L zinc sulfate aqueous solution; the separator was a glass fiber separator (GF, purchased from Olegeeino); and bare zinc (i.e., without the conjugated polymer of the present invention and without a protective layer) was also used as the negative electrode to assemble a zinc-zinc symmetrical battery (electrolyte solution and separator were the same as above). Figures 7-8 Bare-Zn refers to a zinc-zinc symmetric cell assembled with bare zinc as the negative electrode.
[0278] The assembled zinc-zinc symmetric cell was tested at 1 mA cm⁻¹. -2 The battery's long-term cycle performance was studied under charge-discharge conditions, and the test results are as follows: Figure 7 As shown.
[0279] from Figure 7 As can be seen from the data, the battery coated with PNDI7O-2Th material exhibits performance at 1 mA cm⁻¹. -2 Under charge-discharge conditions, the cycle life reaches 360 h, far exceeding that of bare zinc symmetric cells; the battery coated with PNDI7O-2Tz material achieves a cycle life of 360 h at 1 mA cm⁻¹. -2 Under normal charging and discharging conditions, the cycle life exceeds 3000 hours, which is much greater than that of bare zinc and PNDI7O-2Th symmetric batteries.
[0280] The assembled zinc-zinc symmetric battery was charged and discharged under high DOD (68.3%) conditions to study its long-term cycle performance. The test results are as follows: Figure 8 Among them, DOD, or Depth of Discharge, is defined as: single discharge capacity ÷ rated usable capacity of battery × 100%, which characterizes the degree to which the electrode discharge consumes active material.
[0281] Depend on Figure 8 It can be seen that the battery coated with PNDI7O-2Th material has a cycle life of 60 h under high DOD (68.3%) conditions, which is greater than that of the bare zinc symmetric battery; the battery coated with PNDI7O-2Tz material has a cycle life of 800 h under high DOD (68.3%) conditions, which is much greater than that of the bare zinc and PNDI7O-2Th symmetric batteries.
[0282] Furthermore, the conjugated polymer prepared in Examples 1-24 was dissolved in chloroform to form a solution with a concentration of 5 mg / mL, which was then dropped onto a zinc sheet and baked at 80 °C for 30 min to form a protective layer with a thickness of 1 μm, thus obtaining a negative electrode sheet. A zinc-zinc symmetric battery was assembled using the same method described above, and tested under high DOD (68.3%) conditions and at 1 mA cm⁻¹. -2 The battery's long-term cycle performance was studied under charge and discharge conditions, and the results are shown in Table 1 below.
[0283] Table 1 - Cycle performance of zinc-zinc symmetric batteries assembled in different embodiments
[0284]
[0285] It is understood that the technical features of the above embodiments can be combined arbitrarily. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0286] The above are merely preferred embodiments of this application, and only specifically describe the technical principles of this application. These descriptions are only for explaining the principles of this application and should not be construed as limiting the scope of protection of this application in any way. Based on this explanation, any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application, as well as other specific embodiments of this application that can be conceived by those skilled in the art without creative effort, should be included within the scope of protection of this application.
Claims
1. A conjugated polymer containing naphthalimide units with ethylene glycol side chains, characterized in that, The structural formula of the conjugated polymer is shown below: ; Where n is an integer from 2 to 1000, and m is an integer from 2 to 10; Ar can be any of the following substituents: 、 、 、 、 、 、 、 。 2. The conjugated polymer containing naphthalimide units with ethylene glycol side chains as described in claim 1, characterized in that, The conjugated polymer is selected from any one of the compounds shown in the following structural formulas 1 to 24: 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 。 3. A method for preparing a conjugated polymer containing naphthalimide units with ethylene glycol side chains as described in any one of claims 1 to 2, characterized in that, Includes the following steps: Under an inert atmosphere, dibromo monomers, bistrialkyltin monomers, palladium catalysts, copper catalysts and ligands are dissolved in an organic solvent and subjected to Stille polymerization under light-protected and reflux conditions to obtain a conjugated polymer containing naphthalimide units with ethylene glycol side chains. The structural formula of the dibromo monomer is: ; Where m is an integer from 2 to 10; The structural formula of the bis(trialkyltin) monomer is any one of the following structural formulas: 、 、 、 、、 、 、 。 4. The method for preparing the conjugated polymer containing naphthalimide units with ethylene glycol side chains as described in claim 3, characterized in that, The organic solvent is chlorobenzene; The palladium catalyst is tris(dibenzylacetone)dipalladium; The copper catalyst is cuprous iodide; The ligand is tris(o-methylphenyl)phosphine.
5. The method for preparing the conjugated polymer containing naphthalimide units with ethylene glycol side chains as described in claim 3, characterized in that, The molar ratio of the dibromo monomer, the ditrialkyltin monomer, the palladium catalyst, the copper catalyst, and the ligand is 1:1:(0.01~0.05):(0.01~0.05):(0.04~0.2). The concentration of the dibromo monomer in the organic solvent is 0.005~0.1 mmol / L; The Stille polymerization reaction is carried out at a temperature of 110-130 °C for 1-96 h, and more preferably 16-72 h.
6. The method for preparing the conjugated polymer containing naphthalimide units with ethylene glycol side chains as described in claim 5, characterized in that, The molar ratio of the dibromo monomer, the ditrialkyltin monomer, the palladium catalyst, the copper catalyst, and the ligand is 1:1:0.02:0.02:0.08; The concentration of the dibromo monomer in the organic solvent is 0.02~0.06 mmol / L.
7. The application of a conjugated polymer containing naphthalimide units with ethylene glycol side chains as described in any one of claims 1 to 2 as a negative electrode protective layer for an aqueous zinc-ion battery.
8. A zinc-ion battery negative electrode sheet, characterized in that, It includes a negative electrode and a protective layer located on the surface of the negative electrode, wherein the material of the protective layer is a conjugated polymer containing naphthalimide units with ethylene glycol side chains as described in any one of claims 1 to 2.
9. A method for preparing a zinc-ion battery negative electrode sheet as described in claim 8, characterized in that, Includes the following steps: A conjugated polymer containing naphthalimide units with ethylene glycol side chains is dissolved in a solvent to prepare a solution, and the solution is coated on the surface of the negative electrode to form a protective layer on the surface of the negative electrode. The solvent includes at least one of chloroform, hexafluoroisopropanol, and chlorobenzene; The concentration of the conjugated polymer containing naphthalimide units with ethylene glycol side chains in the solution is 1~10 mg / mL.
10. A zinc-ion battery, characterized in that, Including the zinc-ion battery negative electrode sheet as described in claim 8.